Analysis of media use and visualization of mathematics teaching materials based on Batak culture with the help of domino cards - Panjaitan, Dedy Juliandri; Hasibuan, Ahmad Laut; Salayan, Madyunus (AIP conference proceedings, 2024)
The purpose of the research was to determine the impact of using media and visualizing mathematics teaching materials based on Batak culture using dominoes. This research is a qualitative descriptive study. The research subjects were determined by the purpose sampling method. This research was conducted at seven schools in the province of North Sumatra, namely SMP Negeri 40 Medan, SMK Negeri 1 Medan, SMA Private Development, SMK Negeri 1 Sei Rampah, SMP Negeri 7 Tanjung Balai, SMA Al Ma’shum and SMP Negeri 1 Sosopan. To obtain data, the researcher collected data through observation, interviews, and using a questionnaire instrument. Based on the data obtained from interviews, observations, and questionnaires, regarding the use of media and visualization of teaching materials assisted by domino card media, it can be concluded that the use of media and visualization of teaching materials based on Batak traditional culture with the help of domino cards makes learning more active. This is because each group member has a role in carrying out the task. In addition, through the learning process students will form a tolerant and respectful personality. From the use of media and teaching materials, based on media questionnaires and visualization of teaching materials got a good response and has a very good category for domino card media and visualization of teaching materials using the website.